A user study on virtual tutor mobile augmented reality from undergraduate medical student perspectives. - Hassan Basri, Nur Athirah; O. K. Rahmat, Rahmita Wirza; Madzin, Hizmawati; Hod, Rafidah (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2023)
Mobile Augmented Reality (MAR) is another fascinating educational innovation with broad potential. It allows for new educational tactics, particularly in medicine. The concept of MAR can help learning activities in several ways, including allowing faster access to information in the mobile platform, increasing student motivation, making the learning process easier and more efficient, and aiding students in better understanding important concepts. However, three things needed to be considered: interface design, the usefulness of Augmented Reality (AR), technical problems with the use of AR applications, and teacher training on the use of AR applications. Without a well-designed interface and guidance for the students, AR technology can be too complicated to use, especially for those who are not familiar with the technology. An interface should be easy to remember and learnt by the user on how to best